Monetary disequilibria and the Euro/Dollar exchange rate - Dieter Nautz; Karsten Ruth (Deutsche Bundesbank, 2005)
Although stable money demand functions are crucial for the monetary model of the exchange rate, empirical research on exchange rates and money demand is more or less disconnected. This paper tries to fill the gap for the Euro/Dollar exchange rate. We investigate whether monetary disequilibria provided by the empirical literature on U.S. and European money demand functions contain useful information about exchange rate movements. Our results suggest that the empirical performance of the monetary exchange rate model improves when insights from the money demand literature are explicitly taken into account.
Keywords: F31; E41; 330; Euro/Dollar Exchange Rate; Monetary Model; Money Demand Functions; Geldnachfrage; Wechselkurs; Nicht-Walrasianisches Gleichgewicht; Monetäre Wechselkurstheorie; Schätzung; Vereinigte Staaten; EU-Staaten